Future Nonaudit Service Fees and Audit Quality - Causholli, Monika; Chambers, Dennis J.; Payne, Jeff L. (Contemporary Accounting Research, 2014)
Prior to the Sarbanes–Oxley Act of 2002, audit partners experienced economic pressure to grow revenue from the sale of nonaudit services to their audit clients. To an auditor who is highly rewarded for revenue generation and growth, nonaudit services may represent a particularly strengthened economic bond with the client. Prior research shows that, in general, nonaudit service fees received in the current period do not impair audit quality. We examine a different setting. We propose that auditor independence can become impaired, and audit quality compromised, when clients that currently purchase relatively low amounts of nonaudit services, increase their purchases of nonaudit services from the auditor in the subsequent period. We test our prediction in the context of earnings management as a proxy for audit quality, measured by (a) performance‐adjusted discretionary accruals and (b) classification shifting of core expenses. Our results indicate that prior to the Sarbanes‐Oxley Act, rewards to the auditor in the form of future additional nonaudit service fees from current‐year high fee‐growth‐opportunity clients adversely affects audit quality. This effect is particularly strong among companies with powerful incentives to manage earnings. Our findings indicate that regulators should consider the multiperiod nature of the client–auditor relationship when contemplating policies that restrict nonaudit services, as well as the overall environment in which audit partners operate. This might include partner compensation arrangements that put pressure on audit partners to focus on increasing revenue at the expense of audit quality.